Association of Anxiety Awareness with Risk Factors of Cognitive Decline in MCI - Ariela Gigi; Merav Papirovitz (Brain Sciences, 2021)
Studies demonstrate that anxiety is a risk factor for cognitive decline. However, there are also study findings regarding anxiety incidence among people with mild cognitive impairment (MCI), which mostly examined general anxiety evaluated by subjective questionnaires. This study aimed to compare subjective and objective anxiety (using autonomic measures) and anxiety as a general tendency and anxiety as a reaction to memory examination. Participants were 50 adults aged 59–82 years who were divided into two groups: MCI group and control group, according to their objective cognitive performance in the Rey Auditory Verbal Learning Test. Objective changes in the anxiety response were measured by skin conductivity in all tests and questionnaires. To evaluate subjective anxiety as a reaction to memory loss, a questionnaire on “state-anxiety” was used immediately after completing memory tests. Our main finding was that although both healthy and memory-impaired participants exhibited elevations in physiological arousal during the memory test, only healthy participants reported an enhanced state anxiety (p = 0.025). Our results suggest that people with MCI have impaired awareness of their emotional state.